Geographical variation in shell shape of the pod razor shell Ensis siliqua (Bivalvia: Pharidae) - Rufino, Marta M. (2018)
The present study assessed the existence of variation in the shell shape of the pod razor shell (Ensis siliqua) throughout its distributional range in the north- eastern Atlantic. Shells of E. siliqua caught at seven collecting sites (three in Portugal, three in Spain and one in Ireland) were studied by geometric morphometric methods, using both landmark- and contour-based methods. Both approaches (landmarks inside the valves and shell outline) discriminated the shells from Aveiro (centre of Portugal) and Strangford Lough (Ireland) from those caught in the nearby localities (remaining Portuguese and Spanish sites,maximum distance of 550 km by sea). Landmark analysis revealed that shells from Aveiro were more similar to shells from Ireland (*1,500 km far away). Contour anal- ysis revealed that shells from Aveiro had a shape with a comparatively larger height-to-width ratio, whereas shells from Ireland showed a slightly more curved outline than in the remaining sites. Landmark- and contour-based methods provided coherent complementary information, confirming the usefulness of geometric morphometric analyses for discerning differences in shell shape among populations of E. siliqua. A brief review of previous applications of geometric morphometric methods to modern bivalve spe- cies is also provided.